2017
DOI: 10.1166/jnn.2017.12419
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle-Based Probe for Colorimetric Detection of Copper Ions

Abstract: A new ligand 10-mercaptodecyl-1-iminodiacetic acid (MDIA) was synthesized and used to modify gold nanoparticles to provide a simple assay to repeatedly sense Cu²⁺ in the solution at room temperature. This functionalized gold nanosensor was applied for the detection of Cu²⁺ in water samples with sensitivity and simplicity. The chelation/aggregation process is reversible via addition of a strong metal ion chelator such as EDTA. This simple and fast colorimetric sensor is important in the application of copper io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[17] observed that Cu 2+ and Ag + can directionally aggregate the Au NPs modified with turtle acid or 2‐aminopyridine, which indicated that organically modified Au NPs are good colorimetric probes for the detection of metal ions. However, most of the surface modification methods of Au NPs are cumbersome and complex [1820]. Therefore, using unmodified Au NPs as colorimetric probes may be a better choice for the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…[17] observed that Cu 2+ and Ag + can directionally aggregate the Au NPs modified with turtle acid or 2‐aminopyridine, which indicated that organically modified Au NPs are good colorimetric probes for the detection of metal ions. However, most of the surface modification methods of Au NPs are cumbersome and complex [1820]. Therefore, using unmodified Au NPs as colorimetric probes may be a better choice for the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…They are usually time‐consuming, intricate, inconvenient and expensive. Recently, some new detection technologies, including surface plasmon resonance (SPR) , fluorescent probes , colorimetric assays and electrochemical methods , were developed to detect Cu 2+ . Among these methods, electrochemical technology has drawn great attention due to its intrinsic properties that high sensitivity, low cost, easy operation and fast response .…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these methods detect Cu 2+ indirectly and require complex modification . Poor reproducibility and low specificity are inevitable for the other metal ions could coordinate with ligand as well . And detecting Cu 2+ in solution directly cannot get an ideal limit of detection (LOD) through electrochemical techniques for the low concentration of Cu 2+ on the surface of the electrode.…”
Section: Introductionmentioning
confidence: 99%